Korean Constitutional Court and Constitutionalism in Political Dynamics: Focusing on Presidential Impeachment - Kim, Jin Wook (The Constitutional Court of the Republic of Indonesia, 2018)
The Constitutional Court of Korea, which should be a product of the June Democracy Movement in 1987, has transformed Korea's constitutionalism ever since its inception. The recent two impeachment cases decided respectively in 2004 against President Roh and in 2017 against President Park might be classic examples of how the state institutions including the Court interact with other institutions in a very political case in terms of political dynamics. In the impeachment case against President Roh, the Court positioned itself strategically by establishing the 'grave violation of law’ rationale, where it sided with the impeaching parliament by finding three counts of violations of law but dismissed the case in its entirety through the operation of the 'grave violation of law'. In the impeachment case against President Park, the Court basically followed the grave violation logic but reached a different conclusion to remove the President, which might be another strategic position taken by the Court, which is in line with the will of the super-majority of the Korean public. This paper aims to discuss how the Constitutional Court has developed its strategic position in terms of political dynamics, by analyzing the two presidential impeachment cases.